Acetate: a diet-derived key metabolite in energy metabolism. Issue 6 (November 2017) - Canfora, Emanuel E.; Blaak, Ellen E.
Abstract : Purpose of review: To highlight recent research findings on effects of the short-chain fatty acid acetate in the control of body weight, insulin sensitivity, and glucose homeostasis. For this purpose, relevant animal and human in-vivo studies were reviewed and putative mechanisms and pathways were discussed. Recent findings: Animal and human in-vivo studies provide strong indications for a beneficial role of orally ingested or colonically derived acetate, in the energy and substrate metabolism, thereby preventing or reversing the obese insulin-resistant phenotype. However, data from rodents are conflicting and indicate that an increased acetate turnover promotes body weight gain and insulin resistance. A reason for these controversies may be related to the mode and site of acetate administration, as well as to the species and the metabolic phenotype of animals used. Summary: Overall, animal and human data suggest a direct regulatory role of acetate in several pathways involved in energy expenditure and fat utilization. In addition, acetate stimulates the release of gut-derived satiety-stimulating hormones and might regulate the inflammatory state. However, human intervention studies are required to evaluate the recent 'acetate discrepancies' and to confirm whether an increase in the acetate availability is a promising approach for the prevention and management of obesity and associated impairments in glucose and insulin metabolism.